Política e ideologia no discurso sobre a crise da educação: análise dos Parâmetros Curriculares Nacionais do Ensino Médio: as noções de formação e conhecimento - Santos, Hobert Valdir dos (2017)
In this thesis we analyze the meanings attributed to what is known as the crisis of education. Because it is apparently a very broad and diffuse idea, the Delors Report, published in Brazil under the title Education - a treasure to be discovered was adopted as a starting point. The impact of this report was examined in the elaboration of the National Curricular Parameters for High School, specifically regarding this dimensions and perspectives related to the conception of knowledge and qualification. On this aspect, it is analyzed how the understanding of the education crisis was appropriated by the Brazilian government, at that time, in order to implement curricular changes in Secondary School